5(x+6)=4(3-2x)

Simple and best practice solution for 5(x+6)=4(3-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+6)=4(3-2x) equation:


5(x+6)=4(3-2x)

We simplify the equation to the form, which is simple to understand
5(x+6)=4(3-2x)

Reorder the terms in parentheses
+(+5x+30)=4*(3-2x)

Remove unnecessary parentheses
+5x+30=+4+*(+3-2x+)

Reorder the terms in parentheses
+5x+30=+(+12-8x)

Remove unnecessary parentheses
+5x+30=+12-8x

We move all terms containing x to the left and all other terms to the right.
+5x+8x=+12-30

We simplify left and right side of the equation.
+13x=-18

We divide both sides of the equation by 13 to get x.
x=-1.3846153846154

See similar equations:

| f(x)=2x^2+11x | | 3=g | | 11x+6=11x-1 | | 5x+9=-17 | | x+2x-13=2 | | -7q+-14=-84 | | 8b-9=3/4(8b-12) | | 4x-1=2(x-3)+1 | | 2x-4(x-3)=-2+3x-16 | | 5x+6=-45-3x | | 3x+14=28 | | 4*k+m*n=n-3 | | 4x-2x+5=11 | | -3.7= | | 2x-4(x-5)=-2+3x-16 | | (-4)-6=-34 | | 7y-3(y-4)=10 | | 4(3x-7)=-2x | | 4(3x-7)=-2 | | 5x-1-ln(5)=0 | | 4b+-6=-14 | | -3x+5y=-4.5 | | 6(5-3x)=7(10-2x) | | 5(3y+3)-18=17+5y | | -4-6=-34 | | -3x-4=-4x-2 | | x/2+x/8=9 | | 2(3a-2b)=8(6a-3b) | | 11x-1=60 | | 5(a-6)=5a-30 | | -4(4-5x)=124 | | 5x-6=-x+12-3x |

Equations solver categories